The Effect of Economic Growth, Open Unemployment Rate and Human Development Index on Poverty in North Sumatra - Hwan Daniel; Nico Purba; Novia Simamora (Indonesian Journal of Advanced Research, 2023)
This study aims to analyze the effect of economic growth, open unemployment rate and human development index on poverty in North Sumatra in 2015-2022. The data used in this study were sourced from the Central Statistics Agency for North Sumatra Province and were cross section or time series data. The model used in this study was a multiple linear regression model by testing autocorrelation, multicollinearity, normality, heteroscedasticity, F test, T test and test the coefficient of determination (R2). The estimation results show that the Economic Growth Rate Variable (LPE) has a positive and insignificant effect on Poverty, which means that if Economic Growth (LPE) increases it will increase Poverty in North Sumatra Province. The Human Development Index (IPM) variable has a negative and significant effect on poverty, which means that if the Human Development Index (IPM) increases, poverty will decrease in North Sumatra Province. The Variable Open Unemployment Rate (TPT) has a positive and insignificant effect on Poverty, which means that if the Open Unemployment Rate (TPT) increases it will increase Poverty in North Sumatra Province.